FeOOH / MIL-100(Fe) composite material and preparation method and application thereof
Patent Information
- Application Number
- CN202511520694.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-10-23
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2045-10-23
AI Technical Summary
若不经合适处理处置,直接排放会加剧养殖区域水体富营养化、导致近海水域环境生态系统失衡
(1)本发明制备的FeOOH/MIL-100(Fe)复合材能够兼具二者优势实现高效脱氮除磷,对于水体的适应性较强,具有应用于不同pH水体的潜力;此外同时还能够促进微生物生长代谢,通过微生物自身生长所需实现脱氮除磷。
Smart Images

Figure CN121377307B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of water treatment technology, specifically to a FeOOH / MIL-100(Fe) composite material, its preparation method, and its application. Background Technology
[0002] With the development of aquaculture technology, farming methods are shifting towards intensive and multi-dimensional operations. The significant increase in farming scale and density leads to the production of large quantities of feed during the farming process, resulting in wastewater rich in uneaten feed, excrement from farmed organisms, and high concentrations of nitrogen, phosphorus, and organic matter. Direct discharge without proper treatment will exacerbate eutrophication in aquaculture areas and cause imbalances in the nearshore aquatic ecosystem. Because marine aquaculture wastewater is characterized by high salinity and a low C / N ratio, traditional biological denitrification methods are difficult to apply to it.
[0003] Therefore, there is an urgent need to design a suitable packing material to promote the physiological and biochemical reactions of microorganisms for efficient nitrogen and phosphorus removal in aquaculture wastewater. Summary of the Invention
[0004] The purpose of this invention is to provide a FeOOH / MIL-100(Fe) composite material, its preparation method, and its application. Iron-based materials can promote direct interspecies electron transfer among microorganisms, increase the activity of key enzymes involved in anaerobic reactions, optimize the microbial community structure, and enhance the metabolic activity among microorganisms. MIL-100(Fe) possesses excellent catalytic performance, while FeOOH can spontaneously generate in the natural environment. A FeOOH / MIL-100(Fe) heterojunction packing material is designed for efficient nitrogen and phosphorus removal in aquaculture wastewater. The prepared material combines the advantages of both materials: it adsorbs and precipitates phosphorus in aquaculture wastewater; simultaneously, it serves as a packing material for microbial attachment, providing a suitable growth environment for microorganisms and promoting enzyme secretion, thereby enhancing the nitrogen and phosphorus removal functions of microorganisms.
[0005] To achieve the above objectives, the present invention adopts the following technical solution: A method for preparing a FeOOH / MIL-100(Fe) composite filler includes the following steps: (1) Mix ferric chloride hexahydrate, trimesic acid, deionized water and sodium hydroxide solution by sonication for 20-40 minutes. (2) The mixture obtained in step (1) is placed in a stainless steel high-pressure reactor lined with polytetrafluoroethylene for hydrothermal reaction. (3) After the reaction is completed, the precipitate is collected by centrifugation, and the precipitate is placed in deionized water and washed by water bath shaking 2 to 4 times. Then it is soaked and washed with anhydrous ethanol, and finally dried under vacuum to obtain FeOOH / MIL-100(Fe) composite filler.
[0006] Furthermore, the concentration of the sodium hydroxide solution in step (1) is 1M.
[0007] Furthermore, in step (1), the ratio of ferric chloride hexahydrate, trimesic acid, deionized water and sodium hydroxide solution is 5 mM: 3.33 mM: 10 mL: 0.1 mL.
[0008] Furthermore, the temperature of the hydrothermal reaction in step (2) is 150~170°C, and the reaction time is 11~13 h.
[0009] Furthermore, the temperature of the water bath oscillation in step (3) is 70°C, and the oscillation is performed for 2 hours each time.
[0010] Furthermore, the vacuum drying in step (3) is performed at a temperature of 150°C for 6 hours.
[0011] The present invention also provides a FeOOH / MIL-100(Fe) composite filler prepared by the above preparation method and its application in biological nitrogen and phosphorus removal in aquaculture tailwater.
[0012] Furthermore, the FeOOH / MIL-100(Fe) composite filler has a positively charged surface in the pH range of 3 to 11.
[0013] Furthermore, the FeOOH / MIL-100(Fe) composite filler enhances the denitrification and phosphorus removal efficiency by increasing denitrification enzymes, polyphosphokinases, and ATP.
[0014] Furthermore, the denitrifying enzyme is nitrate reductase and nitrite reductase.
[0015] The advantages of this invention are as follows: (1) The FeOOH / MIL-100(Fe) composite material prepared by the present invention can combine the advantages of both to achieve efficient nitrogen and phosphorus removal. It has strong adaptability to water bodies and has the potential to be applied to water bodies with different pH values. In addition, it can also promote the growth and metabolism of microorganisms and achieve nitrogen and phosphorus removal through the growth requirements of microorganisms themselves.
[0016] (2) The FeOOH / MIL-100(Fe) composite material prepared in this invention has a heterojunction structure. FeOOH / MIL-100(Fe) has a large number of channels, a relatively rough surface, and is in the form of octahedral crystals and needle-like crystals. Microorganisms can be loaded on the surface of FeOOH / MIL-100(Fe) to enhance the biological denitrification and phosphorus removal effect.
[0017] (3) The FeOOH / MIL-100(Fe) prepared in this invention can significantly increase the secretion of extracellular polymers and denitrification and phosphorus removal enzymes. At the same time, the material itself has the effect of adsorbing and precipitating phosphorus, which can effectively promote the growth of microorganisms and their denitrification and phosphorus removal. The material is positively charged over a wide pH range, which helps to adsorb microorganisms and carry out physiological activities on their surface. Attached Figure Description
[0018] Figure 1 A physical image of the prepared FeOOH / MIL-100(Fe) material.
[0019] Figure 2 The Fourier transform infrared spectrum of the FeOOH / MIL-100(Fe) composite material prepared in this invention is shown.
[0020] Figure 3 The X-ray diffraction pattern of the FeOOH / MIL-100(Fe) composite material prepared in this invention is shown.
[0021] Figure 4 This is a scanning electron microscope image of the FeOOH / MIL-100(Fe) composite material prepared in this invention.
[0022] Figure 5 The image shows the denitrification effect of the FeOOH / MIL-100(Fe) composite material prepared in this invention.
[0023] Figure 6 The image shows the phosphorus removal effect of the FeOOH / MIL-100(Fe) composite material prepared in this invention.
[0024] Figure 7 This is a comparison diagram of the zeta potential of the FeOOH / MIL-100(Fe) composite material prepared in this invention with other materials.
[0025] Figure 8 This is a comparison chart of the denitrification-related enzyme content of the FeOOH / MIL-100(Fe) composite material prepared in this invention with other materials.
[0026] Figure 9 The FeOOH / MIL-100(Fe) composite material prepared in this invention promotes the content of enzymes related to phosphorus removal by microorganisms.
[0027] Figure 10 The effect of the FeOOH / MIL-100(Fe) composite material prepared in this invention on ATP concentration compared with other materials. Detailed Implementation
[0028] To make the content of this invention easier to understand, the technical solution of this invention will be further described below with reference to specific embodiments, but this invention is not limited thereto.
[0029] Example 1 This embodiment provides a method for preparing FeOOH / MIL-100(Fe) composite material, including the following steps: (1) 1.35g ferric chloride hexahydrate (FeCl3·6H2O), 0.7g pyromellitic acid (H3BTC), 10 mL deionized water and 1M 0.1mL sodium hydroxide solution were ultrasonically mixed. (2) Transfer the mixed solution to a polytetrafluoroethylene reaction vessel, and place the reaction vessel into a stainless steel high-pressure reactor for reaction. The reaction temperature is 160°C and the reaction time is 12 h.
[0030] (3) After removing the reactants, centrifuge (10000 rpm, 10 min), collect the precipitate and place it in deionized water. Wash it three times in a water bath at 70°C for 2 h each time. Then soak it in anhydrous ethanol for 12 h, wash it, and vacuum dry it at 150°C for 6 h to obtain the FeOOH / MIL-100(Fe) composite material.
[0031] Comparative Example 1 This comparative example provides a method for preparing FeOOH, which differs from Example 1 in that it does not involve the use of MIL-100 (Fe) in the preparation process, and includes the following steps: 3.24 g of FeCl3·6H2O and 1.96 g of NaOH were dissolved in 10 mL of deionized water, respectively. Sodium hydroxide solution was then added dropwise to the FeCl3·6H2O solution. The mixture was magnetically stirred at 150 rpm for 10 min. The solution was then transferred to a polytetrafluoroethylene liner, and 20 mL of deionized water was added. The mixture was then transferred to a high-pressure reactor and subjected to a hydrothermal reaction at 100 °C for 6 h. After the reaction was completed, the resulting sample was collected by centrifugation, dried, ground, and stored.
[0032] Comparative Example 2 This comparative example provides a method for preparing MIL-100(Fe), which differs from Example 1 in that it does not involve the use of FeOOH in the preparation process, and includes the following steps: Mix 1.35g FeCl3·6H2O, 0.7g H3BTC and 10 mL of deionized water, place them in a high-pressure reactor lined with polytetrafluoroethylene, and react at 160℃ for 12 h. After the reaction is completed, collect the sample by centrifugation, dry it, grind it and store it.
[0033] Figure 1 A physical image of the prepared FeOOH / MIL-100(Fe) material.
[0034] Figure 2 The infrared spectra of the composite materials prepared in Example 1 and Comparative Examples 1-2 of this invention are shown. The characteristic peaks of the FT-IR spectrum of FeOOH / MIL-100(Fe) are quite similar to those of MIL-100(Fe). The two materials show similar peaks at 1446 cm⁻¹. -1 and 1381cm -1 And 623 cm -1 and 483 cm -1 The absorption peak positions and intensities at 893 cm⁻¹ are close, indicating a tight bond between pyromellitic acid and Fe in the crystal. Furthermore, observation of the FT-IR spectrum of FeOOH / MIL-100(Fe) reveals a peak at 893 cm⁻¹. -1 Absorption peaks also appeared at the point, which is due to the bending vibration of Fe-OH. FT-IR results confirmed the presence of the chemical composition of FeOOH and MIL-100(Fe) in FeOOH / MIL-100(Fe).
[0035] Figure 3 The XRD patterns of the composite materials prepared in Example 1 and Comparative Examples 1-2 of this invention are shown. The main diffraction peak of MIL-100 (Fe) in the figures is located at 2... θ =6.3°(306), 10.3°(505), 11.0°(776), 20.4°(323), indicating the successful synthesis of MIL-100(Fe) with a crystalline structure. The diffraction peaks of FeOOH are located at 2θ=17.8°(79), 21.1°(122), 33.2°(175), 36.5°(195). This indicates the successful preparation of FeOOH crystals, and the prepared FeOOH is... α -FeOOH. It can be seen that the prepared FeOOH / MIL-100(Fe) has the characteristic X-ray diffraction peaks of both MIL-100(Fe) and FeOOH.
[0036] Figure 4The image shown is a scanning electron microscope (SEM) image of the FeOOH / MIL-100(Fe) composite material prepared in Example 1 of this invention. It can be seen that the FeOOH / MIL-100(Fe) exhibits numerous octahedral crystal structures, and the crystal size is relatively dispersed. The surface is also rougher, and fine FeOOH crystals grow on the surface of the FeOOH / MIL-100(Fe) crystals. This is the difference between FeOOH / MIL-100(Fe) and MIL-100(Fe). The rougher surface indicates a larger specific surface area. An increased specific surface area is beneficial for increasing mass transfer of the target substance within the material and its contact with active sites. Furthermore, for microorganisms, an increased specific surface area facilitates contact and adhesion between microorganisms and the composite material, thus enhancing the utilization of the composite material by microorganisms.
[0037] Application Example 1 Add 100 mL of simulated seawater to a 250 mL Erlenmeyer flask, sterilize, and then add each material at a concentration of 50 mg·L⁻¹. -1 and salt-tolerant denitrifying bacteria k5-x (OD) 600 =1.00) 1mL, incubated in a constant temperature shaking incubator for 48h, and samples were taken at regular intervals to test relevant indicators.
[0038] The simulated seawater formulation is as follows: In deionized water, it contains 1.8 g·L⁻¹ Na₃C₆H₅O₇. -1 FeSO4·7H2O = 0.072 g·L -1 KNO3 = 0.724 g·L -1 KH2PO4 = 0.44 g·L -1 NaCl = 24 g·L -1 .
[0039] Salt-tolerant denitrifying bacteria k5-x Extracted from sludge of a wastewater treatment plant in Fuzhou City, detailed information can be found in the paper "MIL-100 (Fe) Coupled with Biological Denitrification for Aquaculture Wastewater Treatment: Enhancement Mechanism and Immobilization Application". Salt-tolerant denitrifying bacteria were used. k5-x Inoculate into 100 mL of broth medium and incubate at 25 °C until OD reaches 100 mL. 600 =1.00.
[0040] Figure 5 This is a graph showing the nitrate removal time relationship of the FeOOH / MIL-100(Fe) composite material prepared in Example 1 of this invention. Salt-tolerant denitrifying bacteria. k5-x The nitrate nitrogen concentration was reduced from 97.30 mg·L⁻¹ within 48 hours. -1Degraded to 49.51 mg·L -1 The degradation rate was 49.1%. After adding FeOOH / MIL-100(Fe), the nitrate nitrogen concentration in the system decreased to 41.19 mg·L⁻¹ after 48 h. -1 The degradation rate was 56.7%, and the degradation rate of nitrate nitrogen increased by 17.4%; moreover, compared with MIL-100(Fe) and FeOOH, FeOOH / MIL-100(Fe) showed better performance than salt-tolerant denitrifying bacteria. k5-x It exhibits better nitrate degradation performance.
[0041] Figure 6 The image shows the phosphorus removal effect of the FeOOH / MIL-100(Fe) composite material prepared in this invention (experimental procedure as above). It can be seen that the FeOOH / MIL-100(Fe) composite material has a strong adsorption and precipitation capacity for phosphate ions, exhibiting a certain treatment effect. When the FeOOH / MIL-100(Fe) composite material and microorganisms are used together for phosphorus removal, rapid removal of phosphate is achieved, with a good removal effect within 24 hours. Furthermore, the removal rate is higher than that of microorganisms or the FeOOH / MIL-100(Fe) composite material alone, achieving highly efficient phosphorus removal.
[0042] Figure 7 This is a comparison of the zeta potentials of the FeOOH / MIL-100(Fe) composite material prepared in this invention with those of MIL-100(Fe) and FeOOH. The isoelectric points of MIL-100(Fe), FeOOH, and FeOOH / MIL-100(Fe) are pH=3.1, pH=6.5, and pH>11, respectively. Within the pH range of 3 to 11, the surface of the FeOOH / MIL-100(Fe) composite material is positively charged and relatively stable. The isoelectric point of microorganisms is usually between pH 3.5 and 4.8. Compared with other materials, the FeOOH / MIL-100(Fe) composite material exhibits positive charge over a wide pH range. The high isoelectric point is conducive to attracting negatively charged microorganisms, making it easier for microorganisms to aggregate on the material. This facilitates better utilization of the active sites on the material surface by microorganisms, enabling it to adapt to different water qualities and showing broader application prospects.
[0043] Application Example 2 After the experiment in Application Example 1 above, 25 mL of the mixture was taken from each bottle, centrifuged at 4000 r / min for 4 min at 4 ℃, the supernatant was discarded, and the precipitate was resuspended in buffer (50 mM Tris-HCl + 5 mM MgCl2, pH 7.8), and the centrifugation and washing were repeated twice; then, the cells were sonicated at 4 ℃ for 5 min to disrupt them, centrifuged at 4000 r / min for 20 min at 4 ℃ to remove large particles; then, the cells were centrifuged at 21000 r / min for 1 h, and the supernatant was taken as the crude enzyme solution. The content of each enzyme in the crude enzyme solution was determined. The control group did not add any materials. The experimental results are shown in […]. Figure 8 and Figure 9 .
[0044] All enzymes and ATP were detected using commercial kits purchased from Shanghai Enzyme-Link Biotechnology Co., Ltd. The batch numbers of the kits are as follows: Nar: 20241102-2541A, Nir: 20241102-2544A, PPK: 20241102-2565A, ATP: 20241102-2560A.
[0045] Figure 8 This is a comparison of the denitrification-related enzyme content of the FeOOH / MIL-100(Fe) composite material prepared in this invention with other materials. The concentrations of nitrate reductase (Nar) and nitrite reductase (Nir) in the experimental group with added FeOOH / MIL-100(Fe) were 106.7 U·L⁻¹. -1 and 76.4 U·L -1 Compared to the control group without added materials, the Nar and Nir contents increased by 60.34% and 38.93%, respectively. Compared to FeOOH and MIL-100(Fe), the Nar and Nir contents increased by 15.52% and 18.12%, and 55.17% and 33.06%, respectively. Compared to other materials, the FeOOH / MIL-100(Fe) composite material had higher Nar and Nir contents, indicating that the FeOOH / MIL-100(Fe) composite material can significantly enhance the denitrification-related enzymes of microorganisms to promote the denitrification process.
[0046] Figure 9The FeOOH / MIL-100(Fe) composite material prepared in this invention promotes the content of enzymes related to microbial phosphorus removal. Polyphosphokinase (PPK) is a key enzyme in bacterial phosphorus removal, capable of transferring phosphorus from water into cells under aerobic or anoxic conditions to achieve biological phosphorus removal. Compared with the control group, the PPK content in the experimental group with added FeOOH / MIL-100(Fe) increased by 71.2%. This indicates that the FeOOH / MIL-100(Fe) composite material can also improve phosphorus removal efficiency by promoting the production of polyphosphokinase by microorganisms.
[0047] Application Example 3 After the experiment in Application Example 1 above, 15 mL of the mixture was taken from each bottle and incubated at 4 °C and 4000 r / min for 4 min, then the supernatant was discarded. 20 mL of buffer solution (20 mmol / L HEPES + 0.25 mol / L sucrose + 2 mmol / L EDTA + 5 mmol / L MgCl2, pH 7.5) was added and vortexed. 0.1 g of cation exchange resin (Dowex 50WX8, purchased from Shengke Biochemical, batch number: 2024010821R) + 0.025 g of polyvinylpyrrolidone was added, vortexed for 10 s, and allowed to stand for 2 min. BAB was added to a final concentration of 0.05%, incubated at 25 °C for 30 s, and immediately placed on ice. The mixture was then incubated at 100 °C for 1 min, and immediately placed on ice. ATP testing was subsequently performed, with the Control group consisting of no added materials.
[0048] Figure 10 The effect of the FeOOH / MIL-100(Fe) composite material prepared in this invention on ATP concentration compared with other materials.
[0049] In the biological treatment of nitrogen and phosphorus in wastewater, the energy supply for microorganisms is crucial, with adenosine triphosphate (ATP) being a key indicator. ATP is the core energy carrier of microbial metabolism and effectively reflects microbial activity. It can be seen that the ATP concentration in the experimental group with added FeOOH / MIL-100 (Fe) was 47.3 nmol·L⁻¹. -1 The ATP concentration in the Control group was only 27.6 nmol·L⁻¹. -1 The addition of FeOOH / MIL-100(Fe) increased ATP secretion by 45.1%. Compared with FeOOH and MIL-100(Fe), FeOOH / MIL-100(Fe) has a more significant promoting effect on ATP production and can better promote the physiological and biochemical processes of microorganisms, thereby improving the effect of denitrification and phosphorus removal.
[0050] The above description is only a preferred embodiment of the present invention. All equivalent changes and modifications made within the scope of the claims of the present invention should be included in the scope of the present invention.
Claims
1. A method for preparing a FeOOH / MIL-100(Fe) composite filler, characterized in that: Includes the following steps: (1) Mix ferric chloride hexahydrate, trimesic acid, deionized water and sodium hydroxide solution by sonication for 20-40 minutes. (2) The mixture obtained in step (1) is placed in a stainless steel high-pressure reactor lined with polytetrafluoroethylene for hydrothermal reaction. (3) After the reaction is completed, the precipitate is collected by centrifugation, and the precipitate is placed in deionized water and washed by water bath shaking 2 to 4 times. Then it is soaked and washed with anhydrous ethanol, and finally dried under vacuum to obtain FeOOH / MIL-100(Fe) composite filler. The concentration of the sodium hydroxide solution mentioned in step (1) is 1M; The ratio of ferric chloride hexahydrate, trimesic acid, deionized water and sodium hydroxide solution used in step (1) is 1.35g:0.7g:10mL:0.1mL; The temperature of the hydrothermal reaction in step (2) is 150~170°C and the reaction time is 11~13 h.
2. The preparation method according to claim 1, characterized in that: The temperature of the water bath oscillation in step (3) is 70°C, and each time is 2 hours.
3. The preparation method according to claim 1, characterized in that: The vacuum drying in step (3) is performed at a temperature of 150°C for 6 hours.
4. A FeOOH / MIL-100(Fe) composite filler prepared by the method according to any one of claims 1 to 3, characterized in that: The FeOOH / MIL-100(Fe) composite filler has a positively charged surface in the pH range of 3 to 11.
5. The application of the FeOOH / MIL-100(Fe) composite packing material as described in claim 4 in biological nitrogen and phosphorus removal from aquaculture tailwater.
6. The application according to claim 5, characterized in that: The FeOOH / MIL-100(Fe) composite filler improves the nitrogen and phosphorus removal efficiency by increasing denitrification enzymes, polyphosphokinases, and ATP.
7. The application according to claim 6, characterized in that: The denitrifying enzymes are nitrate reductase and nitrite reductase.
